Carakde Class Learning Program from the Sigi Community: Evaluation for Improving Student Learning Outcomes - Andi Afrinaramadhani Hatta; Ali Muhtadi (Universitas Negeri Makassar, 2022)
This study aims to determine the suitability of (1) context, (2) input, (3) process, and (4) product of Carakde class learning program carried out by Sahabat Indonesia Berbagi (SIGi Community) in Makassar Region based on predetermined success criteria. This research is an evaluation research with Context, Input, Process, Product (CIPP) approach model and uses quantitative research method. The population in this study is students of Carakde Class of 21 peoples. Sample in this study used purposive sampling. This research used analysis data, descriptive and inferensial statistic. The data analysis technique used statistic t-tes . After being analyzed using statistical formulas, it can be seen that student learning outcomes after the CIPP model evaluation applied. Besides, Context evaluation involves program objectives and program relevance to environmental needs. Input Evaluation encompasses environmental, instrumental, and raw input. This can be seen fromÂ increase in the students' mean scores from pre-test and post-test results. Process evaluation covers the implementation of Carakde Class learning can be seen based on student learning outcomes. The mean value of the pre-test is 39, while the mean value of the post-test is 61.42.Â From these calculations obtained thitung: 11.284 while ttable : 2,086 which means thitung > ttable. So that the alternative hypothesis Ha can be accepted and null hypothesis (Ho) is rejected. This means that student learning outcomes after the CIPP model evaluation is applied. Furthermore, product evaluation comprises the program graduates and the achievement of program objectives.